INFORMATION GIVING BY NURSES IN EMPOWERING PARENTS TO CARE FOR CHILDREN WITH CANCER - Rasmita, Dina (Universitas Nahdlatul Ulama Surabaya, 2023)
Background: Parents empowerment involves accessing information, support, resources, and opportunities for parents to optimize the health of the children with cancer, feel meaningful, determine themselves, become competent, and impact their lives. Nurses play a crucial role in educating and training parents to care for their children. Objective: The purpose of the study was to explore the provision of information by nurses to parents in empowering parents to care for children with cancer based on parents’ perspectives. Methods: The participants involved in this study were six nurses who served in the treatment room for children with cancer selected by purposive sampling technique. Data collection was carried out by in-depth interview method using semi-structured interview guidelines. Data analysis with stages of analysis according to Colaizzi. Result: The results of this study found four themes about the provision of information by nurses in empowering parents, namely information provided by nurses, how to provide information, sources of information, and family responses after being given information. providing information nurses to parents, namely information about room rules and facilities, child care while in the hospital and at home, how to provide information that is often provided by nurses, namely verbally, demonstrations, and media, parents' information sources are nurses, doctors, media, and fellow parents with cancer, and parents' responses after being given information are sad and happy. Conclusion: Nurses need to pay attention to the right time, and the right method, and assess the readiness of parents when providing information so that the information given to parents can be received and understood by parents well.